Diagnostic Delays Lead to Greater Disability in Degenerative Cervical Myelopathy and Represent a Health Inequality. Issue 6 (15th March 2020) - Pope, Daniel H.; Mowforth, Oliver D.; Davies, Benjamin M.; Kotter, Mark R.N.
Abstract : Study Design: Online survey. Objective: This study seeks to quantify delays faced, determine demographics of patients most likely to face delay, and determine whether delays affect surgical management and outcomes. Summary of Background Data: Patients report significant delays in diagnosis of degenerative cervical myelopathy (DCM). Methods: Seven hundred seventy-eighty patients with self-reported DCM recruited via online survey hosted on myelopathy.org. A cumulative odds ordinal logistic regression was run to determine the effects of demographic (sex, country of residence, ethnicity, household income, and educational status) on the delay in diagnosis of DCM. Chi-square tests of homogeneity were run to determine the effects of delayed diagnosis on functional outcomes (patient-derived modified Japanese Orthopaedic Association disability score, support dependence, and employment status) and surgical management (anterior/posterior approach, single-/multilevel surgery). A Kruskal-Wallis H test was used to determine whether delayed diagnosis affected the number of operations undergone. Results: The average delay in diagnosis faced was "1–2 years." Greater delays in diagnosis were faced by Black or African American patients ( P = 0.010). Delayed diagnosis was predictive of greater disability as assessed by patient-derived modified Japanese Orthopaedic Association score ( P = 0.001), support dependence ( P = 0.040), and employment status ( P < 0.0005). Delayed diagnosis did not affect the likelihood of surgery, the number of operations undergone or perioperative characteristics. Conclusion: Patients continue to face significant delays in diagnosis of DCM. Ethnicity significantly influences length of delay experienced. Longer delays do not appear to affect surgical management but are associated with greater disability. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textDelays in the diagnosis of degenerative cervical myelopathy are extensive. Diagnostic delay is associated with greater disability, support-dependence, and unemployment. Black or African American patients are more likely to face delayed diagnosis.